Oral management strategies for radiotherapy of head and neck cancer - Yumiko Kawashita; Sakiko Soutome; Masahiro Umeda; Toshiyuki Saito (Japanese Dental Science Review, 2020)
Summary: Radiotherapy, often with concomitant chemotherapy, has a significant role in the management of head and neck cancer, however, radiotherapy induces adverse events include oral mucositis, hyposalivation, loss of taste, dental caries, osteoradionecrosis, and trismus, all of which have an impact on patients’ quality of life. Therefore, it is necessary to implement oral management strategies prior to the initiation of radiotherapy in patients with head and neck cancer. Since 2014, the National Comprehensive Cancer Network Clinical Practice Guidelines in Oncology (NCCN Guidelines) have enumerated the “Principles of Dental Evaluation and Management (DENT-A)” in the section on head and neck cancers, however, oral management was not explained in detail. Oral management has not been achieved a consensus protocol. The aim of this literature is to show that oral management strategy include removal infected teeth before the start of radiotherapy to prevent osteoradionecrosis, oral care for preventing severe oral mucositis to support patient complete radiotherapy during radiotherapy, and prevent of dental caries followed by osteoradionecrosis after radiotherapy.